The making of the Doric temple architecture, religion, and social change in archaic Greece - Zuchtriegel, Gabriel 1981- (Cambridge University Press, 2023)
"In this volume, Gabriel Zuchtriegel revisits the idea of Doric architecture as the paradigm of architectural and artistic evolutionism. Bringing together old and new archaeological data, some for the first time, he posits that Doric architecture has little to do with a wood-to-stone evolution. Rather, he argues, it originated in tandem with a disruptive shift in urbanism, land use, and colonization in Archaic Greece. Zuchtriegel presents momentous architectural change as part of a broader transformation that involved religion, politics, economics, and philosophy. As Greek elites colonized, explored, and mapped the Mediterranean, they sought a new home for the gods in the changing landscapes of the sixthcentury BC Greek world. Doric architecture provided an answer to this challenge, as becomes evident from parallel developments in architecture, art, land division, urban planning, athletics, warfare, and cosmology. Building on recent developments in geography, gender, and postcolonial studies, this volume offers a radically new interpretation of architecture and society in Archaic Greece"--
Keywords: Geschichte 600 v. Chr.-500 v. Chr.; Religion; Architektur; Sozialer Wandel; Tempelbau; Dorische Ordnung; Griechenland -- Altertum; Temples / Greece; Architecture and society / Greece / History / To 1500; Greece / Civilization / To 146 B.C.; Architecture and society; Civilization; Temples; Greece; To 1500; History